Cobalt Cardiomyopathy Secondary to Hip Arthroplasty: An Increasingly Prevalent Problem - Russel Tilney; Melanie Roberta Burg; Mark Adrian Sammut (Case Reports in Cardiology)
A forty-year-old man experienced worsening heart failure four years following bilateral complicated total hip replacement. His condition was extensively worked up but no underlying pathology was immediately evident. Given the cobalt-chromium alloy component present in the hip arthroplasties, the raised cobalt blood levels, and a fitting clinical picture coupled with radiological findings, the patient underwent right hip revision. Evidence of biotribocorrosion was present on direct visualisation intraoperatively. The patient subsequently experienced symptomatic improvement (NYHA class III to class I) and echocardiography showed recovery of ejection fraction. Cobalt exists as a bivalent and trivalent molecule in circulation and produces a cytotoxicity profile similar to nanoparticles, causing neurological, thyroid, and cardiological pathology. Blood levels are not entirely useful as there is no identifiable conversion factor for levels in whole blood, serum, and erythrocytes which seem to act independently of each other. Interestingly cobalt cardiomyopathy is frequently compounded by other possible causes of cardiomyopathy such as alcohol and a link has been postulated. Definitive treatment is revision of the arthroplasty as other treatments are unproven.